2011
DOI: 10.5897/ajb10.2503
|View full text |Cite
|
Sign up to set email alerts
|

Studies of genetics of yield and yield component characters in F2 and F3 generations of rice (Oryza sativa L.)

Abstract: Three parents with three different durations were crossed in full diallel fashion. The resultant six hybrids were selfed along with their three parents to get six F 2 's. The F 2 's were selfed to obtain six F 3 's. The aforementioned five generations of the six crosses were studied for days to flowering, number of productive tillers per plant, number of filled grains per panicle, 100 seed weight, grain L/B ratio, grain yield per plant and harvest index. The distribution pattern of the segregating generations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(5 reference statements)
1
0
0
Order By: Relevance
“…Transgressive segregation may arise due to the dominance and dominance interaction and also by the additive x additive interaction which is fixable. Similar findings were reported by Thirugnanakumar et al (2011). Both the generation revealed the high mean and wide range of expression of different characters (Table 1 and Table 2) which indicates the presence of sufficient variability existed in the genetic material selected for the study and indicates the scope for selection of suitable breeding material for crop improvement Yadawad et al (2015), Shankarrao et al (2010), Kaushik et al (2013), Maurya et al (2014), Kalimullah et al (2012) and Basavaraj et al (2015) also reported similar results.…”
Section: Resultssupporting
confidence: 92%
“…Transgressive segregation may arise due to the dominance and dominance interaction and also by the additive x additive interaction which is fixable. Similar findings were reported by Thirugnanakumar et al (2011). Both the generation revealed the high mean and wide range of expression of different characters (Table 1 and Table 2) which indicates the presence of sufficient variability existed in the genetic material selected for the study and indicates the scope for selection of suitable breeding material for crop improvement Yadawad et al (2015), Shankarrao et al (2010), Kaushik et al (2013), Maurya et al (2014), Kalimullah et al (2012) and Basavaraj et al (2015) also reported similar results.…”
Section: Resultssupporting
confidence: 92%